SUSCEPTIBILITY OF DIFFERENT CELLS TO RED SEA BREAM IRIDOVIRUS (RSIV) - Ketut Mahardika; Indah Mastuti (Indonesian Aquaculture Journal, 2012)
RSIV is an isolate virus in the genus Megalocytivirus (family Iridoviridae) that has been reported to be pathogen in more than 31 marine fish species in East Asia. The aim of study was to know the susceptibility of several cultured cells to RSIV. RSIV inoculum was inoculated onto cultured cells and then incubated in 25oC. Routine observation of cytopatic effect (CPE) was carried out for 7 days and harvested cells were prepared for virus titration and electron microscopy (EM). The result showed that RSIV grew and propagated in GF (grunt fin), KF-1 (koi fin) and BF-2 (barfin flounder) which caused cytophatic effect as cel ls enlargement. However, RSIV did not propagated on EPC (epithelioma papulosum cyprini), FHM (feathed minnow) and EK-1 (eel kidney) cells. The virus titer were 105.3 TCID50/mL in GF cells, 103.8 and 4.3 TCID50/mL in KF-1, 103.6 and 3.8 TCID50/mL in BF-2, and 7 102.1 TCID50/mL in EPC, FHM and EK-1. The EM observation revealed formation of enlarged cells containing hexagonal virus particles with 140-160 nm in diameter. These results indicated that GF was cultured cell to be optimal for replication of isolate RSIV derived from Ise bay, Mie, Japan.